Gnathological splint therapy in temporomandibular joint disorder - K Gnanashanmugham; B Saravanan; M R Sukumar; T Faisal Tajir (Wolters Kluwer Medknow Publications, 2015)
Temporomandibular joint (TMJ) forms an integral functional part of stomatognathic system. Position, shape, structure and function of teeth have an influence on the proper functioning and health of TMJ. But a problem associated with TMJ is often neglected, and treatment for it is mostly restricted to palliative therapy. A proper understanding of the underlying cause of temporomandibular joint disorder (TMD) is necessary to device a proper treatment plan. Etiology of TMDs varies from idiopathic reasons to systemic disorders. The option of Gnathological splint is a conservative, safe and an effective mode of therapy for TMDs caused by occlusal discrepancies (fulcrum/interferences). This article presents a case report of a patient with TMD caused by occlusal discrepancy